Cultural Content of Mandailing Natal and Interactive Multimedia Integration on Students' Reading Comprehension Performance - Balqis Wandira (Pedagogi: Jurnal Ilmiah Pendidikan, 2026)
This study examined the impact of integrating Mandailing Natal cultural content and interactive multimedia into English instruction at the senior high school level. The participants were 62 Grade X students from MAN 2 Mandailing Natal Regency, divided into experimental and control groups using a pretest-posttest equivalent group design. Data were collected through pretests and posttests measuring students' reading comprehension and were analyzed using mean scores, standard deviation, and paired-sample t-tests. The findings show that the integration of Mandailing Natal cultural content and interactive multimedia significantly improved students' reading comprehension performance, English learning competence, enthusiasm, motivation, and appreciation of cultural heritage. These results indicate that cultural content supported by interactive multimedia is an effective instructional strategy for English learning. Therefore, English textbooks and instructional materials should be revised to include operational procedures and core principles for integrating local cultural content and interactive multimedia.